Problem Child Greece - Georg Quaas (Intereconomics, 2018)
In summer 2018, Greece left the EU rescue umbrella. Enormous efforts were made by the Greek state and its population to cut back its over-consumption and recurring new debt. The austerity measures were associated with numerous reforms aimed at advancing the Greek economy. Doubts that sustainable success was achieved are more than justified. The positive development of net exports, for example, was mainly at the expense of investment. This led to an enormous and uneven reduction of capital stock. With one exception, the structure of investments in capital stock is not optimal and should be readjusted according to the current available data.
Keywords: 330; Debt management; Economic crisis; Greece